GENDER DIFFERENCES AND PERSONALITY TRAITS AS CORRELATES OF PARENTAL INFLUENCE ON CAREER CHOICE AMONG UNDERGRADUATES IN LAGOS STATE - Olabimitan, Benjamin Adegboyega; Adekoya, Toluwalase Samson (African Journal of Social and Behavioural Sciences, 2024)
Deciding on the most appropriate choice of career serves as one of the most important decisions students make in determining their future plans. While often perceived to be an individual choice, a variety of factors are likely to influence one's ultimate career decision. This study investigated gender differences and personality traits as correlates of parental influence on career choice among undergraduates. The study adopted a correlational survey design and randomly selected 281 (48.7%) male and 296 (51.3%) female participants from three universities in Lagos, Nigeria. Two standardized scales were utilized for data collection; a 44-item self-report Big Five Personality Inventory (Goldberg, 1992) with Cronbach coefficient of .76, and 14 14-item scale by Udoh (2012) which sought information on how parental influence on children’s career choice. The results revealed that only agreeableness (r=.285; p>.01), conscientiousness (r=.169; p<.01) and openness to experience (r=.278; p<.01) had significant but weak positive relationship with parental influence on career choice. Also, the difference in means scores of female and male undergraduates was not statistically significant (t= -1.15; df (575); P>.05). The research recommended a policy that will empower the counselling units to continue to educate students on the role of personality in the degree of parental influences on undergraduates’ career choices. Also, this study emphasised the importance of assessing personality traits by counsellors before offering career guidance. In addition, freedom and proper guidance should be given to female undergraduates who intend to venture into areas or careers that are dominated by males.